The Islamic Legal System in Malaysia - Shuaib, Farid Sufian (University of Washington School of Law, 2011)
This article describes the historical evolution and the current structure of the Islamic legal system in Malaysia. The structure of the modern Malaysian state has its roots in the region’s colonial history. By the end of the nineteenth century the territory that comprises contemporary Malaysia had been subjected to British colonial authority. The British did not, however, rule the region as a single colonial unit. In the directly ruled colonies most matters were governed by English common law, and while Islamic doctrine governed family law, it was applied by colonial courts that were staffed by British or British-trained judges. In the colonies subject to indirect rule an English resident exercised authority over matters of British interest while Malay sultans retained their hereditary titles, and local courts exercised the sultan’s authority in matters of Malay adat (custom) and Islam. When the state of Malaysia was created in 1957, the constitution established a federal structure that reflected the pluralistic colonial system. Malaysia is currently comprised of 13 states and three federal territories. Under the constitution, most areas of life are governed by a uniform body of federal law applied by a system of national courts. However, the constitution grants the states the power to apply a version of Islamic law on certain topics enumerated in the constitution, and to create Shari‛a courts to adjudicate disputes involving Muslims relating to matters of Islamic law. The subjects included within the states’ legislative power include, in addition to personal law and matters related to religious practice, offenses deemed to be against the precepts of Islam. All of the states have exercised the powers granted by the constitution to legislate on matters related to Islam, and every state has established Shari‛a courts to adjudicate disputes based on Islamic legislation. A constitutional amendment approved in 1988 eliminated the power of civil courts to hear appeals from decisions of the Syariah courts. At the same time that they are achieving greater autonomy, the Shari‛a courts are also seeking to “upgrade” in ways that emulate the civil courts.